Bortezomib for the treatment of multiple myeloma - Scott, Kathleen; Hayden, Patrick J; Will, Andrea; Wheatley, Keith; Coyne, Imelda (Cochrane database of systematic reviews, 2016)
Multiple myeloma is a malignancy of plasma cells accounting for approximately 1% of cancers and 12% of haematological malignancies. The first-in-class proteasome inhibitor, bortezomib, is commonly used to treat newly diagnosed as well as relapsed/refractory myeloma, either as single agent or combined with other therapies. We conducted a systematic review and meta-analysis to assess the effects of bortezomib on overall survival (OS), progression-free survival (PFS), response rate (RR), health-related quality of life (HRQoL), adverse events (AEs) and treatment-related death (TRD). We searched MEDLINE, the Cochrane Central Register of Controlled Trials and EMBASE (till 27 January 2016) as well as conference proceedings and clinical trial registries for randomised controlled trials (RCTs). We included randomised controlled trials (RCTs) that compared i) bortezomib versus no bortezomib with the same background therapy in each arm; ii) bortezomib versus no bortezomib with different background therapy in each arm or compared to other agent(s) and iii) bortezomib dose comparisons and comparisons of different treatment administrations and schedules. Two review authors independently extracted outcomes data and assessed risk of bias. We extracted hazard ratios (HR) and their confidence intervals for OS and PFS and odds ratios (OR) for response rates, AEs and TRD. We contacted trial authors to provide summary statistics if missing. We estimated Logrank statistics which were not available. We extracted HRQoL data, where available. We screened a total of 3667 records, identifying 16 relevant RCTs involving 5626 patients and included 12 trials in the meta-analyses. All trials were randomised and open-label studies. Two trials were published in abstract form and therefore we were unable to assess potential risk of bias in full.There is moderate-quality evidence that bortezomib prolongs OS (four studies, 1586 patients; Peto OR 0.77, 95% CI 0.65 to 0.92) and PFS (five studies, 1855 patients; Peto OR 0.65, 95% CI 0.57 to 0.74) from analysing trials of bortezomib versus no bortezomib with the same background therapy in each arm.There is high-quality evidence that bortezomib prolongs OS (five studies, 2532 patients; Peto OR 0.76, 95% CI 0.67 to 0.88) but low-quality evidence for PFS (four studies, 2489 patients; Peto OR 0.67, 95% CI 0.61 to 0.75) from analysing trials of bortezomib versus no bortezomib with different background therapy in each arm or compared to other agent(s).Four trials (N = 716) examined different doses, methods of administrations and treatment schedules and were reviewed qualitatively only.We identified four trials in the meta-analysis that measured time to progression (TTP) and were able to extract and analyse PFS data for three of the studies, while in the case of one study, we included TTP data as PFS data were not available. We therefore did not analyse TTP separately in this review.Patients treated with bortezomib have increased risk of thrombocytopenia, neutropenia, gastro-intestinal toxicities, peripheral neuropathy, infection and fatigue with the quality of evidence highly variable. There is high-quality evidence for increased risk of cardiac disorders from analysing trials of bortezomib versus no bortezomib with different background therapy in each arm or versus other agents. The risk of TRD in either comparison group analysed is uncertain due to the low quality of the evidence.Only four trials analysed HRQoL and the data could not be meta-analysed.Subgroup analyses by disease setting revealed improvements in all outcomes, whereas for therapy setting, an improved benefit for bortezomib was observed in all outcomes and subgroups except for OS following consolidation therapy. This meta-analysis found that myeloma patients receiving bortezomib benefited in terms of OS, PFS and response rate compared to those who did not receive bortezomib. This benefit was observed in trials of bortezomib versus no bortezomib with the same background therapy and in trials of bortezomib versus no bortezomib with different background therapy in each arm or compared to other agent(s). Further evaluation of newer proteasome inhibitors is required to ascertain whether these agents offer an improved risk-benefit profile, while more studies of HRQoL are also required.